TRADISI LISAN MASYARAKAT DUSUN BATU URIP SEBAGAI PENGUAT NILAI KEARIFAN LOKAL KOTA LUBUKLINGGAU - Sarkowi, Ira Miyarni Sustianingsih, Yadri Irwansyah (LP4MK STKIP PGRI Lubuklinggau, 2024)
The purpose of this research is to describe and analyze oral traditions in the Batu Urip Hamlet community, Lubuklinggau City, and specifically aims to describe the position of oral traditions in strengthening local wisdom values, the oral traditions that formed Batu Urip Hamlet, and the forms of oral traditions that developed in the Batu Urip community. To reconstruct various interrelated events, this research uses historical research methods which consist of several stages, namely heuristics, criticism, interpretation and historiography. The conclusions of this research show that oral traditions in the Batu Urip community are seen as being able to strengthen local wisdom values ​​for several reasons, including: oral traditions are considered regional identity, oral traditions function as a source of local history, and oral traditions serve as conveying messages and inheritance culture. One form of oral tradition in Batu Urip Hamlet is folklore which explains the origins of Batu Urip Hamlet. Meanwhile, the types of oral traditions that developed in Batu Urip include folklore, nandai, rejung, senjang and regional songs.